1952
DOI: 10.1002/cne.900960108
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the fiber connections of the di‐ and mesencephalon in the cat. II. Fiber connections of the pretectal region and the posterior commissure

Abstract: THIRTEEN FIGURESAlthough the di-and mesencephalon have been the subject of numerous investigations dealing with the anatomy as well as the physiology of these parts of the brain, many points have remained obscure, and among these may be mentioned the delimitation and functional significance of the area of transition between thalamus and tectum opticum, the pretectal region and posterior commissure of this study. I n particular for the pretectal region, configuration and homologies vary from report to report. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1953
1953
1963
1963

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…light labeling appeared in the magnocellular subdivision of the nucleus of posterior commissure (NPCm). This result is consistent with early anterograde degeneration studies that reported NPCm to be more directly implicated in eye movements (Bucher and Bürgi 1952;Carpenter and Peter 1970).…”
Section: Nucleus Of Posterior Commissure (Npc)supporting
confidence: 90%
“…light labeling appeared in the magnocellular subdivision of the nucleus of posterior commissure (NPCm). This result is consistent with early anterograde degeneration studies that reported NPCm to be more directly implicated in eye movements (Bucher and Bürgi 1952;Carpenter and Peter 1970).…”
Section: Nucleus Of Posterior Commissure (Npc)supporting
confidence: 90%